MgCl2 center dot 6PhCH(2)OH - a new molecular adduct as support material for ziegler-natta catalyst: synthesis, characterization and catalytic activity - Gnanakumar, Edwin S.; Thushara, K. S.; Bhange, Deu S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2011)
Benzyl alcohol has been used to prepare a single phase MgCl2 center dot 6BzOH molecular adduct as a support for an ethylene polymerization catalyst (Ziegler catalyst). The structural, spectroscopic and morphological aspects of the MgCl2 center dot 6BzOH molecular adduct and the Ziegler catalyst have been thoroughly studied by various physicochemical characterization techniques. The presence of MgO6 octahedrons due to the interaction of Mg2+ with six -OH groups of the benzyl alcohol is confirmed from a Raman feature at 703 cm(-1), and structural studies. The supported catalyst activity has been evaluated for the ethylene polymerization reaction. The lower polymerization activity of the titanated Ziegler-Natta catalyst compared with a standard catalyst is attributed to the strong interaction of titanium chloride with the support and associated electronic factors.

MgCl2 center dot 4((CH3)(2)CHCH2OH): a new molecular adduct for the preparation of TiClx/MgCl2 catalyst for olefin polymerization - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Dalton Transactions, 2012)
A new molecular adduct of MgCl2 with isobutanol, namely MgCl2 center dot 4((CH3)(2)CHCH2OH) (MgiBOH), has been prepared as a precursor to the supporting material for an olefin polymerization catalyst. The MgiBOH adduct and final titanated Ziegler-Natta catalysts have been thoroughly characterized by powder XRD, thermal analysis, Raman spectroscopy and solid-state NMR for structural and spectroscopy aspects. A peak observed at 712 cm(-1) in the Raman spectra of MgiBOH indicates the characteristic Mg-O-6 breathing mode and the formation of the adduct. The diffraction feature at 2 theta = 7.8 degrees (d = 11.223 angstrom) in the XRD confirms the adduct formation and the layered structure. The aim of the present article is to study how the insertion of a bulky isobutanol moiety affects the structural and electronic properties of the MgCl2 isobutanol molecular adduct. Indeed, the focus of the present study is to explore how the presence of isobutanol, in the initial molecular adduct, influences the final Z-N catalyst properties and its activity.

MgCl2 center dot 6C(6)H(11)OH: a high mileage porous support for ziegler-natta catalyst - Gnanakumar, Edwin S.; Thushara, K. S.; Gowda, Ravikumar R.; Raman, Sumesh K.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2012)
A new and single phase molecular adduct of MgCl2 with six cyclohexanol molecules MgCl2 center dot 6C(6)H(11)OH (MgCyOH) has been synthesized. Structural insight to this adduct was obtained by a variety of physicochemical methods. C-13 CPMAS spectrum and single pulse MAS spectra with high power proton decoupling recorded at different relaxation time showed the presence of two different sets of magnetically unequal cylcohexanol molecules present around Mg2+. A Raman feature of MgCyOH at 712 cm(-1) confirms that cylcohexanol molecules are present around Mg2+ in an octahedral environment. MgCyOH has been used as support material to prepare Ziegler-Natta (Z-N) active catalyst. Textural property of above Z-N catalyst exhibits high surface area (236 m(2)/g) with high porosity. Above active catalyst has been screened for ethylene polymerization. Depending on the cocatalyst employed (Me3Al, Et3Al, and iso-Bu3Al) and ethylene pressure, polyethylene yield varies an order of magnitude, from 378 to 3570 g/g catalyst, indicating a possible creation of different active sites and different interaction between cocatalyst and catalyst.

MgCl2 center dot 6CH(3)OH: a simple molecular adduct and its influence as a porous support for olefin polymerization - Gnanakumar, Edwin S.; Gowda, Ravikumar R.; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (ACS Catalysis, 2013)
A single phase molecular adduct, MgCl2 center dot 6CH(3)OH has been synthesized using MgCl2 and the simplest alcohol, methanol. Structural, spectroscopic, and morphological studies have been carried out for a better understanding of the single phase MgCl2 center dot 6CH(3)OH adduct. C-13 CPMAS solid state NMR studies show all six methanol molecules are magnetically equivalent and present in a single environment around the Mg2+ center. Raman spectral analysis of the characteristic peak at 708 cm(-1) substantiates octahedral coordination of six CH3OH molecules around Mg2+. Solid state C-13 NMR measurements, made after heat treatment at different temperatures, have been utilized to understand the variations in CH3OH stoichiometry and coordination around Mg2+ with temperature. A titanated active catalyst, TiCl4 on MgCl2 center dot 6CH(3)OH, has also been synthesized and subjected to detailed characterizations. The active catalyst shows high surface area (102 m(2)/g) and mesoporosity. The titanated catalyst has been screened for ethylene polymerization reactions using different cocatalysts (R3Al; R= -CH3, -CH2CH3, and -CH2CH(CH3)(2)). A total of 7.25 kg of polyethylene per gram of catalyst has been obtained with Me3Al cocatalyst, which is six times higher in activity compared with commercial Me3Al/TiCl4/MgCl2 center dot 6EtOH-supported orted catalystAlthough porosity influences the catalytic activity, other factors also seem to contribute to the total catalytic activity.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; olefin polymerization; Ziegler-Natta catalyst

Mechanistic aspects of wet and dry CO oxidation on Co3O4 nanorod surfaces: a NAP-UPS study - Ruchi Jain; Gnanakumar, Edwin S.; Gopinath, Chinnakonda S. (ACS Omega, 2017)
Catalytic activity, electronic structure, and the mechanistic aspects of Co3O4 nanorod (NR) surfaces have been explored for CO oxidation in dry and wet atmosphere using near-ambient pressure ultraviolet photoelectron spectroscopy. Presence of water with CO + O2 plummets the catalytic activity because of the change in the electronic nature from predominantly oxide (without water in feed) to a Co3O4 surface covered by a few intermediates. However, at ≥375 K, the Co3O4 surface recovers and regains the oxidation activity, at least partially, even in the presence of water. This is fully supported by the changes observed in the work function of Co3O4 under wet (H2O + CO + O2) conditions compared with dry (CO + O2) conditions. This study focuses on the comparative CO oxidation rate on Co3O4 NR surfaces and highlights the changes in the electronic structure that occur in the catalyst during the CO oxidation reaction.
Keywords: Catalyst; Nano Structures; Power X-Ray Diffraction; spectra; Water Vapor